2019
DOI: 10.34133/2019/1618798
|View full text |Cite
|
Sign up to set email alerts
|

A Photoelectric-Stimulated MoS 2 Transistor for Neuromorphic Engineering

Abstract: The von Neumann bottleneck has spawned the rapid expansion of neuromorphic engineering and brain-like networks. Synapses serve as bridges for information transmission and connection in the biological nervous system. The direct implementation of neural networks may depend on novel materials and devices that mimic natural neuronal and synaptic behavior. By exploiting the interfacial effects between MoS2 and AlOx, we demonstrate that an h-BN-encapsulated MoS2 arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 65 publications
0
30
0
Order By: Relevance
“…The increasing demand for computational power and high cost of specific data transfer speeds between the memory and processors reveal the limitations of von Neumann architecture 1 . In traditional computing systems based on von Neumann architecture, memory and computational units are physically separated and connected by data bus.…”
Section: Introductionmentioning
confidence: 99%
“…The increasing demand for computational power and high cost of specific data transfer speeds between the memory and processors reveal the limitations of von Neumann architecture 1 . In traditional computing systems based on von Neumann architecture, memory and computational units are physically separated and connected by data bus.…”
Section: Introductionmentioning
confidence: 99%
“…Next, we explored 2D α-In2Se3 FeCTs for neural computing, where TG voltage (VTG) spikes simulate presynaptic input and ferroelectric channel current is monitored as post-synaptic current (PSC). TG applies short negative spikes (-8~-5V, step 1V), and with the increase of the spike amplitudes, the FeCTs exhibit incremental PSC amplitudes, but can return to the initial state quickly, which simulates a typical biological short-term plasticity (STP), 10,32 as shown in Figure 4a. TG output and transfer curves are displayed in Figure S5b and Figure S7a respectively in Supporting Information.…”
Section: Raman Characterization Of H-bn Is Shown Inmentioning
confidence: 99%
“…It is widely used in transducers to converse the mechanical energy into electrical energy. Since the piezoelectric effect was discovered by the Curie brothers in 1880, a variety of piezoelectric materials have been invented, which can be separated into the following two categories: (1) inorganic materials, such as ZnO [44], lead zirconium titanate (PZT) [45], barium titanate (BT), modified lead zirconate titanate [46], lead metaniobate, lead niobate barium lithium (PBLN), and modified lead titanate (PT) [47,48]; (2) organic materials, such as polyvinyl chloride (PVC), polyvinylidene fluoride (PVDF) [49] and its derives [50], and some other materials [51][52][53]. All the materials have been studied in fabricating 3 Research PENGs, as shown in Table 1.…”
Section: Materials and Devicesmentioning
confidence: 99%